SYNTHESIS OF IRON OXIDE-MONTMORILLONITE COMPOSITE AND STUDY OF ITS STRUCTURAL STABILITY AGAINTS SULFURIC ACID - Karna Wijaya; Eko Sugiharto; Mudasir Mudasir; Iqmal Tahir; Ika Liawati (Indonesian Journal of Chemistry, 2004)
The synthesis and characterization of iron oxide-montmorillonite and its structural stability test with various concentration of sulfuric acid were conducted. Synthesis was performed by treating Na-montmorillonite clay with oligocations of iron, followed by calcinating the intercalation compound of oligocations-montmorillonite at 200oC for 24 hours. Calcined product was then characterized to determine the iron content, basal spacing and its porosities distribution. To test structural stability againts strong acid (i.e. sulfuric acid), the composites were dispersed into solution of sulfuric acid with various concentration, i.e: 1, 2 and 3M for 24 hours.The characterization result, especially from x-ray-diffractometry analysis, demonstrated that modification of montmorillonite using iron (III)oxide produced so called house of card structure as indicated by its broad, low intensity reflection at 2θ  = 5-6o. The addition of sulphuric acid into composite resulted in probably the formation of face to face arrangements indicated by the appearance of 001 plane reflection. The acid treatment also caused the decrease in the iron content of the iron oxide-montmorillonite as shown by its neutron activated analysis result. The iron content of iron oxide-montmorillonite before the acid treatment was 32,01% w/w, and after the acid treatment was 14.08% w/w (with sulfuric acid of 1M), 6.05% w/w (sulfuric acid of 2M) and 5,98% w/w (with sulfuric acid of 3M), respectively.In general, the sulphuric acid treatment to the composite did not distore the 001 planes of the montmorillonite.